2021
DOI: 10.2147/jmdh.s315553
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Physical Activity Through Reablement for Older Adults: Exploring Healthcare Professionals’ Clinical Reasoning

Abstract: Introduction Reablement is an interdisciplinary, multifactorial, and individualized intervention aimed at improving function and maintaining the independence of community-dwelling older adults who receive home care services. Physical activity (PA) is important for functional ability in older adults, but it is unclear how PA is promoted through reablement. Healthcare professionals’ (HCPs) clinical reasoning and decision-making are essential and determine how reablement is delivered to individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A recent Delphi study among international reablement experts found diverse perspectives on whether or not exercise or motivation to increase PA should be included in reablement, and fewer than half of the experts agreed that exercise and motivation to increase PA should be part of the reablement concept [ 13 ]. Similarly, a recent study by our research team, that built upon the same interviews as the current study, found that HCPs working in reablement in a Norwegian context had diverse perspectives on how PA should be integrated within reablement [ 19 ]. The HCPs had a shared overall perspective that PA involved all types of physical activities, and that daily activities were a core type of PA in reablement.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…A recent Delphi study among international reablement experts found diverse perspectives on whether or not exercise or motivation to increase PA should be included in reablement, and fewer than half of the experts agreed that exercise and motivation to increase PA should be part of the reablement concept [ 13 ]. Similarly, a recent study by our research team, that built upon the same interviews as the current study, found that HCPs working in reablement in a Norwegian context had diverse perspectives on how PA should be integrated within reablement [ 19 ]. The HCPs had a shared overall perspective that PA involved all types of physical activities, and that daily activities were a core type of PA in reablement.…”
Section: Introductionmentioning
confidence: 67%
“…This study is a qualitative exploratory study based on individual interviews, from which one study has been published previously describing some of its methods [ 19 ]. The study design is inspired by a realist perspective, focusing on gaining an increased understanding of mechanisms that may explain why reality unfolds as it does in a particular context [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations